Case Report: Not a Mediastinal Mass! a Ruptured Giant Coronary Aneurysm That Occurred in a Young Man - Yao, Peng; Shen, Cheng; Xu, Zhi-Jie; Lin, Yi-dan (Frontiers in Surgery, 2022)
Introduction: Coronary artery aneurysm (CAA) is a localized coronary artery dilatation that exceeds 1.5 times the diameter of a normal adjacent segment or the largest coronary vessel. When the expansion is greater than 2 cm, it is called a “giant” coronary artery aneurysm. Giant coronary artery aneurysm rupture is extremely rare and fatal. Case presentation: We present a rare case who is a 27 years old male with a giant coronary artery aneurysm rupture but no catastrophic events occurred immediately. He was initially misdiagnosed as having a mediastinal mass. The cardiac ultrasound was negative and the chest Magnetic Resonance Imaging (MRI) suggested mass hemorrhage. But the cardiac CTA showed a giant coronary aneurysm rupture with hematoma formation. He eventually underwent surgery and was followed up for 2 months without complications. Conclusion:We report this case of a ruptured giant coronary aneurysm because of its extremely rare occurrence in coronary artery disease. More rarely, in this ruptured case, there was no immediate catastrophic event, but rather symptoms of compression caused by a pseudo-aneurysm. Preoperative diagnosis remains a clinical challenge, especially in young adults. First, a negative cardiac ultrasound does not completely exclude the possibility of coronary aneurysm rupture; Second, it is very difficult to distinguish this disease from a ruptured mediastinal tumor bleeding, and chest MRI and cardiac CTA are crucial tests. Finally, surgical resection may be the right choice for coronary aneurysm rupture. To facilitate the preoperative diagnosis of this rare coronary aneurysm, more cases need to be reported.